Biopolymer enhanced vegetation establishment and their coupled effects on soil hydro-mechanical properties - Jiayu Gu; Junjun Ni; Yanbo Chen; Yufeng Gao (Soil and Tillage Research, 2026)

Enriching triboelectric signal characteristic toward vibration waveform recognition by electron-beam irradiation - Hu Bian; Fanzheng Zeng; Haoran Yu; Xingyi Song; Jia Liu; Xingke Zhao; Zhenming Chen; Chengmei Gui; Junjun Huang (Chemical Engineering Journal, 2026)

Fusicoccane glycosides from the endophytic fungus Talaromyces sp. DC-26 - Peng Zhou; Jingwen Yu; Xueying Deng; Jinyan Cai; Wenya Feng; Junjun Liu; Qin Li; Chong Dai; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Electrospun chitosan/PCL/Tween-80 nanofibers incorporated with Ocimum basilicum essential oil as bio-based active packaging materials - Qi Liu; Shuqing Wang; Junjun Liang; Hong Chen; Sheng Jiang; Lin Tang (Food Bioscience, 2026)

Roles of desiccation crack depth and surface intensity in affecting clay slope failures during extreme drought-rainfall events - Qi Zhang; Junjun Ni; Yanbo Chen; Yikai Wang; Haiyi Zhong (Engineering Geology, 2026)

Towards complete utilization of rice husk components: A sequential process for the co-production of pectin, xylo-oligosaccharides, lignin-silica hybrid material, and fermentable sugars - Yuanxian Wu; Yuxin Xiao; Ronglian Hua; Keyu Chen; Yuanyuan Zhu; Junhua Zhang; Junjun Zhu (Biomass and Bioenergy, 2026)

Operando lab-on-fiber platform for concurrent monitoring of moisture degradation and lead leakage in perovskite solar cells - Binyun Xia; Weijin Chen; Junjun Jin; Zhengyang Ke; Jiahong Cheng; Xiaoyu Huang; Yanbo Nie; Qidong Tai; Ning Wang (Chemical Engineering Journal, 2026)

Delayed and asymmetric groundwater responses to meteorological forcing across Germany revealed by lagged mutual information - Fangfei Cai; Funing Ma; Zhenxue Dai; Junjun Chen (Journal of Hydrology, 2026)

Engineered norfloxacin-derived carbonized polymer dots for synergistic antibacterial and anti-inflammatory periodontitis therapy - Xinyu Jiang; Yu Deng; Jia Liu; Huan Chen; Hongyan Lin; Yu Zhong; Junjun Liu; Xinchan Liu; Bai Yang (Chemical Engineering Journal, 2026)

Regulation spin state in CuCo2O4 nanozyme by heterojunction construction with polyoxometalate for detoxiﬁcation of mustard gas simulants - Junjun Lu; Xinxin Xu; Jin Chen; Qiang Wang (Journal of Hazardous Materials, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Microwave digestion-ICP-MS coupled with molecular docking: unraveling elemental distribution and its correlation with glucose and fructose accumulation in 25 strawberry cultivars - Jiayue Xu; Hao Chen; Yang Ni; Yingying Zhang; Junjun Yang; Chen Feng; Guixia Wang; Rong Xiong (Food Chemistry, 2026)

Autonomous inverse modeling of complex groundwater systems via a physics-integrated large language model multi-agent framework - Funing Ma; Junjun Chen; Zhenxue Dai; Fangfei Cai; Yingtao Hu (Water Research, 2026)

Genome-wide identification of MATE gene family in potato and functional characterization of StMATE1/4/98 in response to aluminum stress - Junjun Huang; Guanzhuo Wang; Chang Yuan; Xin Chen; Juanjuan Yu; Huiling Gong; Huahua Wang (Plant Science, 2026)

Integrated chemometrics and untargeted metabolomics reveal the differential effects of drying methods on the quality of Sharen (Amomum villosum Lour.) - Zhixia Sun; Jun Chen; Junjun He; Ivan Shorstkii; Liqing Du; Taotao Dai; Yihui Wang; Yanli Yao; Chengmei Liu; Lizhen Deng (Food Bioscience, 2026)

Enzymatically synthesized native-like guaiacyl dehydrogenation polymer as a formaldehyde-free adhesive for high-strength, water-resistant plywood - Rui Luo; Wenhao Liu; Qian Tu; Yuanpu Wang; Junjun Chen; Junxian Xie; Rong Zhang; Nianjie Feng; Peng Wang (Chemical Engineering Journal, 2026)

Mining and characterization of novel prolyl endopeptidases from human gut microbes for degrading the immunogenic gluten 33-mer peptide - Xiaojing Zhou; Pan Huang; Chuan Zhang; Chengcheng Zhang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Junjun Wu; Xiaomei Lyu; Fengwei Tian; Jianxin Zhao; et al. (Food Bioscience, 2026)

Reassessing the efficacy and safety of trimethoprim-sulfamethoxazole for Pneumocystis jirovecii pneumonia: a retrospective study - Yangmin Hu; Wei Hu; Danyang Li; Fen Lan; Wei He; Meng Chen; Difei Yao; Junjun Xu; Yujin Lai; Haibin Dai (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Influence of calcium-based localized flocculation near drainage body on dredged sludge consolidation under vacuum preloading - Jun Chen; Xingbing Li; Junjun Ni; Guizhong Xu; Chao Liu (Marine Georesources & Geotechnology, 2026)

Multiscale simulation and machine learning sensitivity analysis of pore-structure controls on solute transport in heterogeneous porous media - Sida Jia; Yuyang Huang; Junjun Chen; Zhongjun Ma; Jian Tian; Zhenxue Dai (Journal of Hydrology, 2026)

Antibiotic pollution impedes nitrogen elimination rates and increases N2O emission from wetlands: A multilevel meta-analysis and the mechanisms - Jibao Jia; Yaxin Chen; Yang Li; Yuting Jiang; Deshou Cun; Yun Zhou; Shengjiong Deng; Junjun Chang (Journal of Environmental Chemical Engineering, 2026)

Plantaricin-producing Lactiplantibacillus plantarum NDF28B2 as an adjunct culture enhances fermented Milk texture and suppresses Listeria monocytogenes - Nan Xiao; Yang Liu; Chengcheng Zhang; Chuan Zhang; Pan Huang; Gang Wang; Shumao Cui; Wenwei Lu; Bo Yang; Junjun Wu; Xiaomei Lyu; Fengwei Tian; et al. (Food Research International, 2026)

Monoclonal antibody production based on different chelators and development of time-resolved fluorescent microsphere lateral flow immunoassays for lead detection - Mengxin Zhou; Haojie Chen; Junjun Huang; Yingxiang Nie; Lehong Qin; Zhuohui Pan; Zhili Xiao (Food Chemistry, 2026)

Fabrication of extracorporeal mechanical energy harvesting and implantable triboelectric nanogenerators for self-powered medical devices - Zhenni Liu; Hu Bian; Cong Lin; Quan Chen; Jia Liu; Zhenming Chen; Jun Chen; Dongdong Fang; Junjun Huang (Chemical Engineering Journal, 2026)

A soybean EIN transcription factor confers resistance to Phytophthora sojae and favorable agronomic traits - Meng Liu; Jiaxin Yin; Xudong Wei; Junjun Song; Yaqun Dongye; Xi Chen; Xin Fang; Xinyue Yu; Yan Sun; Jihao Ju; Xiaoyu Chen; Junjiang Wu; et al. (Plant Cell Reports, 2026)

Experimental and numerical study of the extreme behavior of double concave friction pendulum bearings - Mingke Li; Rajesh P. Dhakal; Junjun Guo; Zhongguo Guan; Xingqin Chen (Engineering Structures, 2026)

Deciphering the regulatory role of the pfs gene on biofilm formation in Lactobacillus plantarum R: Insights from transcriptome and metabolome - Xin Fan; Bo Li; Xinao Xu; Binbin Long; Zhiwen Jia; Ran Wang; Junjun Gao; Yang Chen; Mingye Peng; Mengzhou Zhou (Bioresource Technology, 2026)

Ball-milling pretreatment-driven low-temperature waste cotton fibers-based hard carbon anodes for sodium-ion batteries - Yingying Zhou; Tiantao Huang; Zixin Lv; Che Wang; Junjun Peng; Aiping Jin; Jun Xiong; Linghui Yu; Ming Li; Zhongchen Ma; Jinchao Wei; Qing Chen (Biomass and Bioenergy, 2026)

Combining compost and biochar facilitates moisture improvements and plant growth under field conditions - Viroon Kamchoom; Sumetha Chaisarn; Junjun Ni; Zhongkui Chen; Natdanai Sinsamutpadung; Xun Wen Chen (Plant and Soil, 2026)

Effects of multi-source solid waste-based stabilizing materials on the improvement of high-salinity silt - Yongsheng Yao; Chen Liu; Yuchen Wang; Xiyan Chen; Jue Li; Junjun Ni (Transportation Geotechnics, 2026)

An effective 3D inversion algorithm of CSEM and its application in geothermal exploration - Ningbo Bai; Zhiqiang Chen; Bo Han; Junjun Zhou; Wenlong Zhou; Guoshu Huang; Xiangyun Hu (Physics of the Earth and Planetary Interiors, 2026)

Physically crosslinked polyphenol-chitosan edible coating for the application of walnut kernels during roasting - Xinhui Wang; Junjun Zhou; Bing Qi; Zhou Chen; Siting Li; Aijin Ma; Yingmin Jia (Food Chemistry, 2026)

Enhanced osteogenic differentiation of rBMSCs under low-frequency dynamic stimulation of piezoelectric membranes - Jing Liu; Donglin Li; Xiaoqing Liu; Jiahao Zeng; Yuxuan Lu; Weiqiang Fan; Shuncheng Zhang; Yuxuan Jia; Linxuan Zheng; Xin Chen; Hongzhang Deng; Yongmei Wang; et al. (Chemical Engineering Journal, 2026)

A multi-scale geometric feature-adaptive density-aware framework for robust sub-conductor segmentation in high-voltage transmission corridors - Yueqian Shen; Chenyang Zhang; Jinhu Wang; Jinguo Wang; Junjun Huang; Yanming Chen (Advances in Space Research, 2026)

L-amino acids modulate biofilm formation, UV resistance, and insecticidal activity in Bacillus thuringiensis formulations: Mechanisms and optimization - Zixuan Wang; Yimeng Zhang; Junjun Chen; Qingqing Liu; Xueqin Luo; Qiuting Xu; Hongxin Su; Yanyan He; Fang Xiong; Shuang Lin; Tianpei Huang; Xiong Guan (Pesticide Biochemistry and Physiology, 2026)

Integrating multi-stage interventions for harmful algal blooms effective management - Zhuwu Jiang; Jianxin Pan; Chengchun Shi; Xiao Yao; Huang Yu; Junjun Wang; Junjun Chen; Jyunhong Shen; Hai Yu; Wuqiang Zeng; Junlan Chen; Zhihao Lin; et al. (Journal of Environmental Management, 2026)

Distinct phylogenetic patterns and assembly processes of abundant and rare taxa in traditional grain vinegar fermentation ecosystem - Mingye Peng; Bo Li; Yunli Zhu; Lu Guo; Lei Deng; Zhicong Shen; Zhiwen Jia; Yang Chen; Junjun Gao; Mengzhou Zhou (International Journal of Food Microbiology, 2026)

Deep eutectic solvents driving innovation in pulping technology and upgrading of dissolving pulp: A review - Junxian Xie; Shiyun Zhu; Haitao Yang; Jun Xu; Peng Wang; Junjun Chen (Bioresource Technology, 2026)

Impact of observation and surrogate-model noises on deep learning-based subsurface heterogeneous structure identification through monitoring network optimization - Yuzhou Xia; Chuanjun Zhan; Zhenxue Dai; Jichun Wu; Xiaoying Zhang; Huichao Yin; Jiahe Yan; Junjun Chen; Zihao Wang; Mohamad Reza Soltanian; Kenneth C. Carroll (Advances in Water Resources, 2026)

Environmental impact and carbon footprint analysis of rural domestic wastewater treatment plants based on life cycle assessment method: A case study of Fuzhou City, China - Hanwei Huang; Xiaoying Lin; Junjun Chen; Xueping Liu; Zushan Zhuo; Yuqi Li (Journal of Water Process Engineering, 2025)

Greenhouse gas emissions from field-scale surface-flow constructed wetlands fed with different polluted water types: Environmental and microbial drivers - Deshou Cun; Xiaowan Chen; Junjun Chang; Yang Li; Rong Wu; Rufeng Lin; Shengjiong Deng; Erik Jeppesen; Changqun Duan (Journal of Hydrology, 2025)

Red mud-modified biochar as an enhancer for solidification/stabilization of chromium(VI)-contaminated soil: Effects of pyrolysis temperature, feedstock, and dosage - Tao Chen; Bin He; Junjun Ni; Saif Ullah (Journal of Environmental Chemical Engineering, 2025)

Elucidating the mechanism of sulfur reactions over NiFe2O4 oxygen carrier at atomic level - Cheng Shen; Yu Li; Daifen Chen; Xin Liu; Junjun Sun; Jintian He; Laihong Shen (Fuel, 2025)

Experimental study and seismic performance analysis of novel damage-free self-centering devices with variable stiffness, high-energy dissipation and low prestress - Xin Li; Hui Jiang; Liangjiang Chen; Junjun Guo; Yongzheng Zhou; Wenliang Lu; Cong Zeng (Engineering Structures, 2025)

The CD40/CD40L Pathway Regulates the Aggressiveness of Ovarian Cancer Cells via the Activation of Regulatory B Cells - Shanshan Ma; Pengfei Chen; Suyang Guo; Liangliang Wang; Jialin Hu; Junjun Shao (Biochemical Genetics, 2025)

Impact of groundwater extraction intensity on the monitoring design for seawater intrusion in heterogeneous coastal aquifers - Funing Ma; Junjun Chen; Zhenxue Dai; Fangfei Cai; Dayong Wang; Yue Ma (Journal of Hydrology, 2025)

Road safety performance of a new W-beam guardrail system with rubber sandwich layer under vehicle collisions: Experimental and numerical studies - Zongwang Xie; Rui Wang; Hui Zhao; Shuo Xu; Wensu Chen; Junjun Ren (Engineering Structures, 2025)

The effect of stratus clouds on aerosol distribution in South China based on aircraft measurements - Jianqiu Gao; Zhujie Li; Junxia Li; Gang Wang; Chang Chen; Songwei He; Zhiyuan Shu; Shaoyu Hou; Junjun Lin (Atmospheric Research, 2025)

Interactively Integrating Reach and Grasp Information in Macaque Premotor Cortex - Junjun Chen; Guanghao Sun; Yiwei Zhang; Weidong Chen; Xiaoxiang Zheng; Shaomin Zhang; Yaoyao Hao (Neuroscience Bulletin, 2025)

Genetic analysis and localization of aroma candidate genes for rice - Junjun Guo; Xueyu Yang; Liang Gao; Jin Chen; Liang Zhang; Chunlong Zhang; Bo Zhang; Chuyi Wang; Dandan Li; Juan Li; Shihuang Pu; Jiangli Zhang; et al. (Euphytica, 2025)

Coupling renewable energy with urban greening: quantifying the sustainable development potential of photovoltaic-green roofs - Taoyu Chen; Yantong Li; Yi Zhang; Hexu Ji; Xinyu Wang; Junjun He; Qunyue Liu; He Zhang (Sustainable Cities and Society, 2025)

High chemodiversity of nitrogen-containing organic compounds in vehicle emissions driven by transformative reactions - Shuang Chen; Yisheng Xu; Dandan Liu; Junjun Deng; Rui Liu; Shaofei Kong; Pingqing Fu (Journal of Hazardous Materials, 2025)

Polyphenol-based coacervate droplets as building blocks for protocells and prototissues - Qi Xie; Wei Chen; Zijian Huang; Yuan Gao; Haoyu Zhang; Zhanhao Zhou; Samira Batur; Chuansheng Fu; Jiao Zhang; Conglian Yang; Junjun Liu; Li Kong; et al. (Chemical Engineering Journal, 2025)

Hotspot regions of reactive oxygen species production and their environmental impacts in periodically flooded soil environments: A review - Xing Liu; Yvjie Xie; Paul N. Williams; Baoying Wang; Haiyi Chen; Xiaotong Li; Li Zhang; Leyi Wang; Junjun Liu; Yingxin Wu; Jun Luo (Critical Reviews in Environmental Science and Technology, 2025)

Erosion processes of lahar travelling on volcanic sediments: Insights from the physical and numerical modeling - Shengwu Qin; Jiangfeng Lv; Shuangshuang Qiao; Junjun Chen; Feng Wan; Jingyu Yao; Guangjie Li; Lingshuai Zhang (CATENA, 2025)

The combined effects of convective entrainment and orographic drag on precipitation over the Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Xiaoqi Xu; Xianghua Wu; Lei Zhu; Xin He; Shiying Wu; Pengcheng Lin (Science China Earth Sciences, 2025)

Effects of dietary long-chain polyunsaturated fatty acids on osmoregulation and salinity adaptation in red tilapia (Oreochromis mossambicus♀ × O. niloticus♂) under salinity stress - Jiaying Xie; Junjun Sun; Yuanyou Li; Shuqi Wang; Douglas R. Tocher; Cuihong You; Zhenqiang An; Dizhi Xie; Cuiying Chen (Fish Physiology and Biochemistry, 2025)

Harnessing FDA-approved dipyridamole to inhibit NLRP3 inflammasome and improve outcomes of acute lung injury in sepsis - Xiuhui Chen; Yutong Zheng; Xiaofeng Zhang; Anran Zheng; Junjun Huang; Guoliang Deng; Xuna Wu; Yuying Peng; Xiaoling Zhang; Renshan Chen; Qing Xiao; Weijun Ye (Toxicology and Applied Pharmacology, 2025)

Effects of norfloxacin on the interaction between duckweed and its growth-promoting bacterial assemblages - Hong Lin; Junjun Chang; Tianning Liang; Chen Yang; Yingying Wei; Wei Peng; Ankun Xu; Changqun Duan; Yonggui Zhao (Journal of Hazardous Materials, 2025)

Evolutionary repeatability of chromatin accessibility in the hippocampus between echolocating bats and soft-furred tree mice - Luye Shi; Yuanshuo Ma; Qinyang Hua; Junjun Hao; Qin Zhang; Yaxin Ye; Lu Yang; Qi Liu; Peng Chen; Zhen Liu; Peng Shi (Science China Life Sciences, 2025)

Shear strength of biopolymer amended soil under freeze-thaw cycles: Experimental investigation and DEM modeling - Jiayu Gu; Junjun Ni; Shusen Liu; Yanbo Chen (Engineering Geology, 2025)

A multiple‐behaviors virtual fish model for simulating fish trajectory in vertical slot fishways - Xiaolong Chen; Xiaotao Shi; Xingyong Deng; Majid Rasta; Junjun Tan; Yu Wang; Yongqiang Jiang; Yanqin Bai (Journal of Fish Biology, 2025)
Fishways are essential for restoring river connectivity and facilitating fish migration, necessitating ongoing research for efficiency optimization. This study developed a fish behavior model to optimize fishway efficiency cost‐effectively. The model simulates swimming trajectories of Schizothorax wangchiachii within a vertical slot fishway incorporating upstream behavior, random behavior, obstacle avoidance, and swimming speed variations. The simulated trajectory exhibits a high consistency with 20 real trajectories, achieving a trajectory overlap rate of 86.7%. This result highlights the model's ability to accurately simulate fish movements, demonstrating its significant potential to revolutionize fishway design.

A review of the research progress in the enrichment of rare earth resources by biosorbents - Shiyu Shao; Junjun Wang; Hao Zhou; Xinyi Yu; Jue Kang; Min Huang; Zhu Chen; Hongbo Zhao; Guanzhou Qiu; Li Shen (Minerals Engineering, 2025)

Effects of chitosan on restoring spermatogenesis in mice: Insights from gut microbiota and multi-omics analysis - Guitian He; Boqi Zhang; Tong Chen; Caomeihui Shen; Nan Wang; Junjun Yang; Fuqiang Chang; Yue Sui; Xuanqi Yin; Yueying Wang; Sihui Wang; Yaqiu Li; et al. (Food Research International, 2025)

Sustainable Fe(II) oxidation/reduction and release/recovery dual cycle in a multi-chamber Fe(III)/Peroxymonosulfate electrochemical system: Application, mechanism, and optimization - Minghao Yu; Meng Chen; Chenxu Yang; Jianrui Niu; Jing Zhang; Situ Mu; Ruina Zhang; Junjun Ma; Chun Liu (Chemical Engineering Journal, 2025)

Tenacissoside G reverses paclitaxel resistance by inhibiting Src/PTN/P-gp signaling axis activation in ovarian cancer cells - Jiudong Hu; Yujie Hu; Xiangqi Zhang; Jingxian Zhang; Yangyun Zhou; Xiaohe Wang; Wenhui Wu; Junjun Chen; Yonglong Han (Journal of Natural Medicines, 2025)

Facile fabrication of micro-nano structure on Polydimethylsiloxane film surface for enhancing material recognition accuracy of machine learning-assisted triboelectric nanogenerator - Junjun Huang; Wenlong Chen; Yuting Zong; Zhenming Chen; Honglin Li; Ning Zhang; Chengmei Gui; Xin Jiang (Chemical Engineering Journal, 2025)

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Incartrilactones A and B: Two schinortriterpenoids with a 14,15-seco-15,17-cyclolancifoartane skeleton from Schisandra incarnata - Ying Gao; Juan Chen; Junjun Liu; Zijian Huang; Xiaogang Peng; Wanpeng Li; Chunlun Qin; Hanli Ruan (Phytochemistry, 2025)

Characteristic aroma identification of differentially colored peach fruits based on HS-SPME-GC–MS - Chen Feng; Yang Ni; Yingying Zhang; Junjun Yang; Rong Xiong (Food Chemistry, 2025)

Pea power against microbes: Elucidating the characteristics and antimicrobial mechanisms of antimicrobial peptides obtained through enzymatic hydrolysis of pea protein isolate - Jiake Wang; Tongliang Yang; Wenwen Yu; Junjun Zhou; Yaqing Bian; Shuhong Li; Ye Chen (Food Bioscience, 2025)

Redefining limits: Impact of nozzle diameter on film flow and atomization beyond the synchronizing radius - Yu Tan; Xudong Chen; Maojiang Jia; Bin Ding; Junjun Wu; Yuelin Qin (Chemical Engineering Journal, 2025)

Acid triggering highly-efficient release of reactive oxygen species to block mitochondrial-mediated homeostasis maintenance for accelerating cell death - Yuxin Yang; Shen Wang; Xingxing Chen; Xuetao Wu; Junjun Wang; Yingcui Bu; Chang Xu; Qiong Zhang; Xiaojiao Zhu; Hongping Zhou (Analytica Chimica Acta, 2025)

An integrated framework of deep learning and entropy theory for enhanced high-dimensional permeability field identification in heterogeneous aquifers - Mingxu Cao; Zhenxue Dai; Junjun Chen; Huichao Yin; Xiaoying Zhang; Jichun Wu; Hung Vo Thanh; Mohamad Reza Soltanian (Water Research, 2025)

Trust rebuilding through village co-construction - Junjun Li; Luan Chen; Ye Long; Jin Wang; Xun Li (Journal of Rural Studies, 2025)

The cost of rural environmental degradation in China: An integrated evaluation framework and city-level case study - Wentao Lu; Huihui Zhao; Ye Qiang; Junjun Chen; Yang Guan; Guosheng Wang; Changbo Qin (Environmental Impact Assessment Review, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Silicon alleviates aluminum toxicity by promoting citrate secretion and reducing aluminum accumulation in the cell wall of soybean roots - Junjun Huang; Ruoyi Wang; Ying Wang; Yiwei Chen; Huanan Li; Huahua Wang (Acta Physiologiae Plantarum, 2025)

Desalination of dye and protein by Ba2+/Ca2+ co-crosslinked alginate filtration membrane loaded on polypropylene non-woven - Ningning Gao; Qian Zhang; Yingqi Fan; Zhihui Chen; Yue Zhang; Junkui Gao; Junjun Shi; Huiguo Wang; Kongyin Zhao; Ligang Lin (Desalination, 2024)

Study on the characteristics of urban background ozone pollution based on long-term observations from mountain sites in China during 2015–2022 - Wei Zhao; Bo Gao; Junjun Deng; Jiaren Sun; Laiguo Chen; Shaojia Fan (Atmospheric Research, 2024)

Fine mapping and candidate gene mining of QSc/Sl.cib-7H for spike compactness and length and its pleiotropic effects on yield-related traits in barley (Hordeum vulgare L.) - Jinhui Wang; Yanyan Tang; Jin Li; Juanyu Zhang; Furong Huang; Qiang Li; Baowei Chen; Li’ao Zhang; Tao Li; Haili Zhang; Junjun Liang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2024)

Two genes encoding a bacterial-type ABC transporter function in aluminum tolerance in soybean - Junjun Huang; Huanan Li; Yiwei Chen; Xiaoyu Li; Ziyu Jia; Kunxia Cheng; Luyu Wang; Huahua Wang (Plant Cell Reports, 2024)

Macrophage migration inhibitory factor reversed senescent phenotype in human chondrocytes in vitro - Zhenlan Fu; Qingqing Li; Peiyao Jiang; Xiongbo Song; Junjun Yang; Guangxing Chen; Xiaoyuan Gong; Liu Yang (Molecular Biology Reports, 2024)

Silicon alleviates aluminum-induced programmed cell death through regulating the antioxidant defenses in soybean roots - Yuanyuan Yu; Ying Wang; Huanan Li; Yiwei Chen; Junjun Huang; Huahua Wang (Biologia, 2024)

A review of cleaner production of glass-ceramics prepared from MSWI fly ash - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Junjun Wu; Bin Ding (Journal of Environmental Management, 2024)

Structural disorder Triggered by small organic molecules Boosting δ-MnO2 cathode for Ultra‐Stable aqueous zinc ion batteries - Junjun Tang; Shuan Ma; Yu Jiang; Lufeng Yang; Jie Chen; Xuemin Yan; Bohong Chen; Zhenxiong Huang (Chemical Engineering Journal, 2024)

Triboelectric signal enhancement via interface structural design and integrated with deep learning for real-time online material recognition - Cheng Shen; Jingyi Chen; Yue Liu; Zhenming Chen; Junjun Huang (Chemical Engineering Journal, 2024)

Research on seawater dissolved oxygen prediction model based on improved generative adversarial networks - Ying Chen; Hongbo Zhang; Chongxuan Xu; Qiguang Zhu; Mingfa Cai; Junjun Yuan (Ocean Modelling, 2024)

N-doped carbon achieved by pyrolyzing urea and active carbon for the capacitive deionization coupled PMS oxidation system - Meng Chen; Chenxu Yang; Minghao Yu; Mengyao Han; Zihan Meng; Tian Zhao; Jianrui Niu; Situ Mu; Jing Zhang; Junjun Ma; Chun Liu (Desalination, 2024)

Analysis of the critical parameters for tritiated water entrained moist gas emission from nuclear power station - Xi Xu; Kefeng Lv; Yang Li; Xudan Ma; Hualei Jiang; Chunhua Chen; Junjun Zhang (Annals of Nuclear Energy, 2024)

Soil methane uptake is tightly linked to carbon dioxide emission in global upland ecosystems - Junjun Wu; Long Chen; Hong Zhang; Xiaoxiang Zhao; Xiaoli Cheng; Kerong Zhang; Guihua Liu (Agriculture, Ecosystems & Environment, 2024)

Multi-chamber membrane capacitive deionization coupled with peroxymonosulfate to achieve simultaneous removal of tetracycline and peroxymonosulfate reaction byproducts - Minghao Yu; Chenxu Yang; Meng Chen; Yunke Li; Kexin Kang; Cheng Wang; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Journal of Hazardous Materials, 2024)

Optimization of the intermediate chamber improves desalination performance in flow electrode capacitive deionization (FCDI): A comparative study - Yunke Li; Chenxu Yang; Meng Chen; Yonghuan Bian; Jianrui Niu; Situ Mu; Jing Zhang; Chun Liu; Junjun Ma (Desalination, 2024)

Experimental and theoretical study on performance of Cu-Fe spinel supported with certain inerts during chemical looping combustion - Yu Li; Li Wang; Daifen Chen; Jing Liu; Wei Fan; Junjun Sun (Chemical Engineering Journal, 2024)

Integration of surface-based and space-based atmospheric CO2 measurements for improving carbon flux estimates using a new developed 3-GAS inversion model - Shu'an Liu; Xiaofeng Pan; Xiangyun Xiong; Tianle Sun; Lin Xue; Huifang Zhang; Junjun Fang; Jingchun Fang; Guchun Zhang; Hui Xu; Baozhang Chen (Atmospheric Research, 2024)

Optimization and mechanism studies for the biosorption of rare earth ions by Yarrowia lipolytica - Li Shen; Xinyi Yu; Hao Zhou; Junjun Wang; Hongbo Zhao; Guanzhou Qiu; Zhu Chen (Environmental Science and Pollution Research, 2024)

Temporal variations in dissolved organic matter properties in a eutrophic lake under water dilution and aquatic plant litter decomposition: A simulated microcosm study revealing the environmental and microbial driving factors - Rong Wu; Haoyu Wang; Wei Li; Xiaowan Chen; Qichao Zhou; Junjun Chang (Journal of Water Process Engineering, 2024)

Evaluation of biological activity and prebiotic properties of proanthocyanidins with different degrees of polymerization through simulated digestion and in vitro fermentation by human fecal microbiota - Xiaoyi Chen; Shuai Liu; Hong Song; Chunlong Yuan; Junjun Li (Food Chemistry, 2024)

Enhancing stand establishment and yield formation of cotton with multiple drip irrigation during emergence in saline fields of Southern Xinjiang - Jianlong Dai; Zhengpeng Cui; Yanjun Zhang; Lijie Zhan; JunJun Nie; Jianqiang Cui; Dongmei Zhang; Shizhen Xu; Lin Sun; Bing Chen; Hezhong Dong (Field Crops Research, 2024)

Effects of bed pumice content on lahar erosion: An example from Changbaishan volcano, China - Shengwu Qin; Jiangfeng Lv; Shuangshuang Qiao; Junjun Chen; Jingyu Yao; Feng Wan; Shuaiying Peng; Gohar Rehman; Xiaowei Liu (Engineering Geology, 2024)

Modulation of evapotranspiration and stream runoff by weathered bedrock in arid and semi-arid mountains - Pengfei Lin; Peng Zhao; Jian Ma; Junjun Yang; Xi Zhu; Quanyan Tian; Jun Du; Longfei Chen; Zhibin He (Science of The Total Environment, 2024)

Marine fuel restrictions and air pollution: A study on Chinese ports considering transboundary spillovers - Xiaohong Chen; Junjun Zhou; Yangjie Wang (Marine Policy, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Structure, stability and in vitro digestion of a novel zein-based oil gel delivery system loaded β-carotene - Siqi Qiang; Junjun Zhou; Tongliang Yang; Jiake Wang; Ye Chen; Guiyun Chen; Shuhong Li (Journal of Food Engineering, 2024)

Carbon felt (CF) acted as an “ionic capacitor” to enhance flow electrode capacitive deionization (FCDI) desalination performance - Yunke Li; Junjun Ma; Minghao Yu; Jianrui Niu; Jiarong Gu; Meng Chen; Puming Zhang; Jing Zhang; Chun Liu (Desalination, 2024)

Devonian integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Wenkun Qie; Kun Liang; Wen Guo; Biao Gao; Junjun Song; Bo Chen; Pu Huang; Li Qiao; Honghe Xu; Jitao Chen; Yucong Sun; Yichun Zhang (Science China Earth Sciences, 2024)

9,9′-epoxylignans from Syringa pinnatifolia: A typical case of stereochemical assignment by a quantum chemical calculation with MAEΔΔ parameter - Shungang Jiao; Changxin Liu; Panlong Chen; Junjun Li; Jingjing Sun; Xiaoli Gao; Xingyun Chai (Phytochemistry, 2024)

Chae-type cytochalasans from coculture of Aspergillus flavipes and Chaetomium globosum - Wenjing Wang; Junguo Huang; Liangxiu Liao; Xiaolong Yang; Chunmei Chen; Junjun Liu; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2024)

Comparison of biosorption behavior and mechanism of La3+, Sm3+, Y3+, Nd3+, Er3+ by Aspergillus niger and Bacillus sp - Hao Zhou; Junjun Wang; Shiyu Shao; Xinyi Yu; Jue Kang; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Journal of Water Process Engineering, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Trends in global ambient fine particulate matter pollution and diabetes mortality rates attributable to it in the 1990–2019: 30 years systematic analysis of global burden of disease - Junjun Ye; Jilin Li; Liping Li; Shuo Zhang; Jingxian Chen; Dan Zhu; Chuanyan Zhang; Bin Xie; Bangzhou Zhang; Kaijian Hou (Science of The Total Environment, 2024)

The incidence of asthma attributable to temperature variability: An ecological study based on 1990–2019 GBD data - Qingsong Xu; Qinfeng Zhou; Junjun Chen; Tong Li; Junxiong Ma; Runming Du; Mintao Su; Jing Li; Ming Xu; Shengzhi Sun; Jing Ma; Murugappan Ramanathan; et al. (Science of The Total Environment, 2023)

Small molecule linoleic acid inhibiting whey syneresis via interact with milk proteins in the fermentation of set yogurt fortified with c9,t11-conjugated linoleic acid - Junjun Qing; Cheng Peng; Hongbing Chen; Haixing Li; Xiaohua Liu (Food Chemistry, 2023)

Knowledge, Attitude, and Practice of Breast Cancer Patients Toward Lymphedema Complications: Cross-Sectional Study - Yan Qin; Junjun Lu; Shanze Li; Jie Huang; Wenjing Teng; Yue Wu; Wanqing Chen; Lizhen Wang; Weikang Zhu (Journal of Cancer Education, 2023)

Increasing amounts of midwestern Tibetan Plateau vortices and their response to soil moisture distribution coupled with different synoptic systems - Yuxin Kuang; Jie Zhang; Zishu Miao; Zhiheng Chen; Junjun Li; Miaomiao Niu; Shiying Wu; Rui Hu (International Journal of Climatology, 2023)
Tibetan Plateau Vortices (TPVs) are important synoptic systems that affect precipitation over the Tibetan Plateau (TP) and downstream weather. By using daily reanalysis data provided by ECMWF and the objective identification methods, the study identified the basic spatiotemporal changes of TPVs, clustered the TPVs by different dynamic circulation types and explored the dynamic circulation background of the classified TPVs in the midwestern TP and their relationship with thermal factors, such as sensible heat and soil moisture. The results show that TPVs in the midwestern TP exhibited an increasing trend from May to August, resulting from the coupling of dynamics with thermal forcing. The related synoptic circulations were divided into four types according to the dynamic circulations: the shortwave trough, the longwave trough, the shear line and the plateau anticyclone type. Among the TPVs, the percentage of TPVs in the shortwave and longwave trough type was relatively large, accounting for 48.7% and 31.5%, respectively, both of which were dominated by the coupling of increased sensible heat and decreased soil moisture. The shear line type was less affected by thermal factors, and mainly driven by dynamic factors, whereas the soil moisture gradient was responsible for the plateau anticyclone type. The simulation experiment also proved this conclusion.

Enhancing sustainable valorization: Harmless synergistic melting treatment for high-value vitreous products from MSWI fly ash and electrolytic manganese residue - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Bin Ding; Junjun Wu (Waste Management, 2023)

Seasonal purification efficiency, greenhouse gas emissions and microbial community characteristics of a field-scale surface-flow constructed wetland treating agricultural runoff - Xiaowan Chen; Shengjiong Deng; Bohua Ji; Suqing Wu; Junjun Chang (Journal of Environmental Management, 2023)

Stabilizing Cr(Ⅲ) deriving from tannery sludge with kaolin and organic matter - Junjun Ma; Tao E; Shuyi Yang; Liang Chen; Ying Cheng; Jia Yu; Yun Li (Environmental Research, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Reducing uncertainties in hydromechanical modeling with a recently developed Rosetta 3 podeotransfer function - Wei Shao; Sijie Chen; Meijun Li; Ye Su; Junjun Ni; Jianzhi Dong; Yonggen Zhang; Zongji Yang (Engineering Geology, 2023)

Enhanced metal−promoter interaction over Na modified Co2C nanoprisms for high-efficiency hydrogen production from methanol steam reforming - Zilong Shao; Shunan Zhang; Chaojie Huang; Haozhi Zhou; Junjun Chen; Yuhan Sun; Hui Wang (Chemical Engineering Journal, 2023)

Highly sensitive, wide-pressure and low-frequency characterized pressure sensor based on piezoresistive-piezoelectric coupling effects in porous wood - Jingjing Luo; Feihua Liu; Ao Yin; Xue Qi; Jiang Liu; Zhongqi Ren; Shiqiang Zhou; Yuxin Wang; Yang Ye; Qingzhi Ma; Junjun Zhu; Kang Li; et al. (Carbohydrate Polymers, 2023)

The reduced Siberian spring snow cover modulation on southward northernmost margin of East Asia summer monsoon - Shiying Wu; Jie Zhang; Junjun Li; Zhiheng Chen; Yun Hang; Miaomiao Niu; Yuxin Kuang; Rui Hu (Climate Dynamics, 2023)

Reduce uncertainty in soil hydrological modeling: A comparison of soil hydraulic parameters generated by random sampling and pedotransfer function - Wei Shao; Sijie Chen; Ye Su; Jianzhi Dong; Junjun Ni; Zongji Yang; Yonggen Zhang (Journal of Hydrology, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Covalent-crosslinking IRMOF-3-NH2/PVC ultrafiltration membrane for simultaneous removal of bisphenol A and Cd2+ ions in water - Yong Pan; Wei Huang; Yong Zhou; Feng Liu; Chen Zhu; HaiXia Pang; JunJun Tan; BaoMing Xu (Journal of Cleaner Production, 2023)

A non-thermal modification method to enhance the encapsulation efficiency, stability, and slow-release performance of zein-based delivery systems – Cold plasma - Junjun Zhou; Yaqing Bian; Tongliang Yang; Jiake Wang; Tianai Kong; Yifu Zhang; Ye Chen; Shuhong Li (Journal of Food Engineering, 2023)

Multiple biological activities and biosynthesis mechanisms of specific conjugated linoleic acid isomers and analytical methods for prospective application - Suhong Li; Liangwei Xu; Junjun Qing; Xiaodan Wu; Haixing Li; Hongbing Chen; Xiaohua Liu (Food Chemistry, 2023)

Inversion of TEM measurement data via a quantum particle swarm optimization algorithm with the elite opposition-based learning strategy - Junjun Jiao; Jiulong Cheng; Yuben Liu; Haiyan Yang; Dingrui Tan; Peng Cheng; Yuqi Zhang; Chenglin Jiang; Zhi Chen (Computers & Geosciences, 2023)

Improving cold-adaptability of mesophilic cellulase complex with a novel mushroom cellobiohydrolase for efficient low-temperature ensiling - Ming Gong; Ying Wang; Dapeng Bao; Shan Jiang; Hongyu Chen; Junjun Shang; Xiaojun Wang; Hnin Hnin Yu; Gen Zou (Bioresource Technology, 2023)

Thin sheets of bean curd treated by cold plasma: Changes in surface structure and physicochemical properties - Tongliang Yang; Yuhe Wang; Bowen Yang; Yifu Zhang; Jiake Wang; Siqi Qiang; Junjun Zhou; Shuhong Li; Ye Chen (Innovative Food Science & Emerging Technologies, 2023)

Prediction for odor gas generation from domestic waste based on machine learning - Yuanyan Jiang; Jiawei Huang; Wei Luo; Kejin Chen; Wenrou Yu; Wenjun Zhang; Chuan Huang; Junjun Yang; Yingzhou Huang (Waste Management, 2023)

Diverse lignans with protective effect against hypoxia/oxidative injuries to H9c2 cells from Syringa pinnatifolia Hemsl. - Shungang Jiao; Xiaoli Gao; Junjun Li; Ruifei Zhang; Shana Wuken; Changxin Liu; Suyile Chen; Pengfei Tu; Luqi Huang; Xingyun Chai (Phytochemistry, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

Spectrum and mortality of opportunistic infections among HIV/AIDS patients in southwestern China - Sirun Meng; Qiao Tang; Zhiman Xie; Nianning Wu; Yingmei Qin; Rongfeng Chen; Xiaoyu Chen; Xiu Chen; Yueqi Li; Minjuan Shi; Li Ye; Hao Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
We describe the opportunistic infections (OIs) of HIV/AIDS to understand the spectrum, mortality, and frequency of multiple coinfected OIs among HIV/AIDS patients in southern China, where OIs are severe. We carried out a retrospective cohort study of hospitalized HIV-infected individuals at the Fourth People’s Hospital of Nanning, Guangxi, China, from Jan. 2011 to May. 2019. The chi-square test was used to analyze cross-infection; the Kaplan‒Meier analysis was used to compare mortality. A total of 12,612 HIV-infected patients were admitted to this cohort study. Among them, 8982 (71.2%) developed one or more OIs. The overall in-hospital mortality rate was 9.0%. Among the patients, 35.6% coinfected one OI, and 64.4% coinfected more than two OIs simultaneously. Almost half of the patients (60.6%) had CD4 + T-cell counts < 200 cells/μL. Pneumonia (39.8%), tuberculosis (35.3%), and candidiasis (28.8%) were the most common OIs. Coinfected cryptococcal meningitis and dermatitis are the most common combined OIs. The rate of anaemia (17.0%) was highest among those common HIV-associated complications. Multiple OIs are commonly found in hospitalized HIV/AIDS patients in southwestern China, which highlights the need for improved diagnosis and treatment.

Impacts of regional uplift of the Tibetan Plateau on local summer precipitation and downstream moisture budget: A simulation study - Kai Yang; Jinghua Chen; Chunsong Lu; Junjun Li; Tianyu Liu; Liping Deng; Yanwei Li (International Journal of Climatology, 2022)
Using the Weather Research and Forecasting (WRF) model, a series of sensitivity experiments were conducted to study the individual and overall effects of the various topographic uplifts of the Tibetan Plateau (TP) on regional climate variability. The presence of the southern slope of the TP facilitates the maintenance and development of the South Asia High (SAH), which produces a positive cyclic response between local precipitation and SAH, so that the northern branch of the South Asian summer monsoon (SASM) maintains the water vapor supply. At the same time, the southern slope of the TP has a positive effect on the mid‐latitude tropospheric anomalous cyclone and anticyclone systems which promotes the downstream advancement of the East Asian summer monsoon (EASM) and is favourable for the transfer of water vapor and convective clouds downstream. The role of the TP platform is mainly due to the lifting of moisture generated by its local heating, which favours the formation of local convective clouds and precipitation while causing nonadiabatic warming of the troposphere. Water vapor transported from the TP could affect precipitation in central‐eastern China (CEC). However, the supply of water vapor in Southern East China (SEC) mainly comes from the southeast coast of China. The Tibetan Plateau sensitive areas (TPSA) have impacts on the water vapor transport path. Removing the TPSA favours an increase in precipitation and convective clouds in SEC. The removal of topographic disturbances favours the convergence and dispersion of water vapor at mid‐latitudes. The mid‐latitude dynamical anomaly may form a standoff with the low‐latitude dynamical system. This leads to inefficient precipitation and convective generation processes, a weakened monsoon advance over land, and a southward shift in the rainfall belt.

Effect and Mechanism of Cotrimoxazole Against Talaromyces marneffei in vitro - Jie Chen; Rongfeng Chen; Wudi Wei; Fengxiang Qin; Xiu Chen; Jinhao He; Hong Zhang; Gang Wang; Minjuan Shi; Tongxue Qin; Yinlu Liao; Yuting Wu; et al. (Mycopathologia, 2022)

Field investigation and numerical modelling of gas extraction in a heterogeneous landfill with high leachate level - Haijian Xie; Shuangke Fei; Haijie He; An Zhang; Junjun Ni; Yun Chen (Environmental Science and Pollution Research, 2022)

Numerical model for static chamber measurement of multi-component landfill gas emissions and its application - Haijian Xie; Xinru Zuo; Yunmin Chen; Huaxiang Yan; Junjun Ni (Environmental Science and Pollution Research, 2022)
The quantitative assessment of landfill gas emissions is essential to assess the performance of the landfill cover and gas collection system. The relative error of the measured surface emission of landfill gas may be induced by the static flux chamber technique. This study aims to quantify effects of the size of the chamber, the insertion depth, pressure differential on the relative errors by using an integrated approach of in situ tests, and numerical modeling. A field experiment study of landfill gas emission is conducted by using a static chamber at one landfill site in Xi’an, Northwest China. Additionally, a two-dimensional axisymmetric numerical model for multi-component gas transport in the soil and the static chamber is developed based on the dusty-gas model (DGM). The proposed model is validated by the field data obtained in this study and a set of experimental data in the literature. The results show that DGM model has a better capacity to predict gas transport under a wider range of permeability compared to Blanc’s method. This is due to the fact that DGM model can explain the interaction among gases (e.g., CH 4 , CO 2 , O 2 , and N 2 ) and the Knudsen diffusion process while these mechanisms are not included in Blanc’s model. Increasing the size and the insertion depth of static chambers can reduce the relative error for the flux of CH 4 and CO 2 . For example, increasing the height of chambers from 0.55 to 1.1 m can decrease relative errors of CH 4 and CO 2 flux by 17% and 18%, respectively. Moreover, we find that gas emission fluxes for the case with positive pressure differential ( ∆P in-out ) are greater than that of the case without considering pressure fluctuations. The Monte Carlo method was adopted to carry out the statistical analysis for quantifying the range of relative errors. The agreement of the measured field data and predicted results demonstrated that the proposed model has the capacity to quantify the emission of landfill gas from the landfill cover systems.

Analysis on the hotspot characteristics of bird diversity distribution along the continental coastline of China - Peng Hou; Junjun Bai; Yan Chen; Jing Hou; Jiajun Zhao; Yutiao Ma; Jun Zhai (Frontiers in Marine Science, 2022)
Global climate change and disturbances from human activities lead to habitat loss and changes in habitat quality, resulting in a reduction in biodiversity. The continental coastline of China distributes some cities with highly developed economies and coastal wetlands with rich biodiversity, and both economic development and biodiversity conservation are important topics. In order to clarify the spatial distribution of bird biodiversity in coastal areas, based on the MaxEnt model and GIS spatial analysis, the distribution data of 488 species of birds and 15 environmental variables were used to simulate the suitable distribution areas of birds, and to analyze the spatial distribution and hotspots of bird biodiversity in coastal areas. The main findings of this study are as follows. (1) A total of 488 species in 249 genera of 21 orders and 81 families of birds were involved in the modeling of coastal areas. The main environmental factors affecting the potential distribution of birds in general are: land use, monthly mean diurnal temperature range, and precipitation of the driest month. (2) High value areas of bird richness are distributed in different locations in the four sea areas: In the Bohai Rim region, they are mainly distributed in the Liaohe Estuary Wetland in Liaoning Province, the vicinity of the Yongdingxin River and Haihe River in Tianjin, the eastern part of Tianjin, and the Yellow River and Yellow River Delta Wetland in Shandong Province; In the coastal area of the Yellow Sea, they are primarily found in Kunyu Mountain National Nature Reserve, Laoshan Provincial Nature Reserve in Shandong Province, and Yancheng Wetland Rare Birds National Nature Reserve in Jiangsu Province; In the coastal areas of the East China Sea, they are mainly found at the mouth of the Yangtze River, at the national nature reserve of Dongtan birds on Chongming Island, along the southeastern coast of Zhejiang Province, near the Min River and along the coast of Quanzhou in Fujian Province; In the coastal areas of the South China Sea, they are mainly distributed in the Pearl River Delta wetlands of Guangdong Province, the southeastern coastal areas of the Guangdong-Hong Kong-Macao Greater Bay Area, and the Shiwanda Mountain National Nature Reserve in Guangxi Province. (3) The spatial trends in the distribution of hotspots of birds of national priority protection in coastal areas are generally consistent, but more concentrated than the distribution of all birds. (4) After the high-value areas of bird richness were superimposed with protected areas, it was found that the intersecting area accounted for a small proportion of the protected area, and many areas near the inland had low bird richness. Finally, the findings provide references for bird biodiversity conservation and planning in coastal areas.

Effects of soil–plant-biochar interactions on water retention and slope stability under various rainfall patterns - Charles Wang Wai NG; Haowen GUO; Junjun NI; Qi ZHANG; Zhongkui CHEN (Landslides, 2022)

Application of a two-step sampling strategy based on deep neural network for landslide susceptibility mapping - Jingyu Yao; Shengwu Qin; Shuangshuang Qiao; Xiaowei Liu; Lingshuai Zhang; Junjun Chen (Bulletin of Engineering Geology and the Environment, 2022)

Joint Inversion and Application of DC and Full-Domain TEM with Particle Swarm Optimization - Yi Dong; Jiulong Cheng; Haijun Xie; Fei Li; Junjie Xue; Laifu Wen; Zhi Chen; Junjun Jiao (Pure and Applied Geophysics, 2022)

Geochemical characteristics and source of crude oil in the Shenhu uplift, Pearl River Mouth Basin, South China Sea - Xiaoyan Fu; Shijia Chen; Xin He; Junjun You; Hui Li; Mingzhu Lei (Arabian Journal of Geosciences, 2022)

Identification of the vertical sealing of faults by geochemical methods—taking the Zhu-3 sub-basin of the Pearl River Mouth Basin as an example - Xiaoyan Fu; Shijia Chen; Junjun You; Hui Li; Mingzhu Lei (Arabian Journal of Geosciences, 2022)

LncRNA NEAT1 Enhances Glioma Progression via Regulating the miR-128-3p/ITGA5 Axis - Jiakai Chen; Handong Wang; Junjun Wang; Wenhao Niu; Chulei Deng; Mengliang Zhou (Molecular Neurobiology, 2021)
Accumulating evidences indicate that long non-coding RNA nuclear paraspeckle assembly transcript 1 (NEAT1) promotes the progression of glioma. In this study, we postulated that NEAT1 may act as a miR-128-3p sponge. Relative levels of NEAT1 and miR-128-3p expression in human glioma samples and GBM cells were detected using quantitative real-time PCR. By means of CCK-8 assays, transwell assays, and flow cytometric analysis, the biological functions of miR-128-3p and NEAT1 were investigated in U87MG and U251MG human GBM cell lines with stable miR-128-3p and NEAT1 knockdown or overexpression. The luciferase reports, RNA pull-down assay, and RNA immunoprecipitation assay were conducted to determine the relevance of NEAT1 and miR-128-3p in glioma. As a result, high expression of NEAT1 and lack of miR-128-3p were observed in glioma specimens and cells. By binding to anti-oncogene miR-128-3p in the nucleus, NEAT1 enhanced tumorigenesis and glioma development. Further experiments suggested that ITGA5 expression was increased in glioma tissues and was found to be connected with miR-128-3p. Additionally, NEAT1 facilitated ITGA5 expression via competitively binding to miR-128-3p. For this reason, ITGA5 would not be decomposed by miR-128-3p and could activate FAK signaling pathway, thereby promoting cell growth. Collectively, these results indicated that the NEAT1/miR-128-3p/ITGA5 axis was involved in glioma initiation and progression, and might offer a potential novel strategy for treatment of glioma.

A Modified Self-adaptive Method for Mapping Annual 30-m Land Use/Land Cover Using Google Earth Engine: A Case Study of Yangtze River Delta - Le’an Qu; Manchun Li; Zhenjie Chen; Junjun Zhi (Chinese Geographical Science, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Temporal variability of free-living microbial culturability and community composition after an Akashiwo sanguinea bloom in Shenzhen, China - Huirong Chen; Junjun JIang; Fajun Jiang; Shuangfei Li; Zhangli Hu (Ecotoxicology, 2021)

Devonian-Carboniferous boundary in China - Wenkun Qie; Yuanlin Sun; Wen Guo; Ting Nie; Bo Chen; Junjun Song; Kun Liang; Baoan Yin; Shupeng Han; Junying Chang; Xiangdong Wang (Palaeobiodiversity and Palaeoenvironments, 2021)

MiR-874 Inhibits Cell Proliferation, Migration, and Invasion of Glioma Cells and Correlates with Prognosis of Glioma Patients - Yongjuan Li; Xiaoyan Chen; Wei Xue; Junjun Liang; Liang Wang (NeuroMolecular Medicine, 2021)

Deep Dermatophytosis Caused by Trichophyton rubrum - Junjun Sang; Kai Guo; Xingfeng Qi; Hongkun Wang; Shengping Chen (Mycopathologia, 2021)

Nrf2 deficiency aggravates the kidney injury induced by subacute cadmium exposure in mice - Chengjie Chen; Xue Han; Gang Wang; Dan Liu; Lina Bao; Congcong Jiao; Junjun Luan; Yongyong Hou; Yuanyuan Xu; Huihui Wang; Qiang Zhang; Hua Zhou; et al. (Archives of Toxicology, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

Synthesis of 4-oxotetrahydropyrimidine-1(2H)-carboxamides derivatives as capsid assembly modulators of hepatitis B virus - Nicky Hwang; Haiqun Ban; Junjun Chen; Julia Ma; Hui Liu; Patrick Lam; John Kulp; Stephan Menne; Jinhong Chang; Ju-Tao Guo; Yanming Du (Medicinal Chemistry Research, 2021)

Astragaloside protects rat brain from microwave-induced functional injuries via restoring acetylcholine and normalizing electroencephalogram - Li Zhao; Yunbo Sun; Chao Yu; Junjun Chen; Xinping Xu; Xueyan Zhang; Hui Wang; Jing Zhang; Haoyu Wang; Ji Dong; Binwei Yao; Hongmei Zhou; et al. (Environmental Science and Pollution Research, 2020)

How do Biotic and Abiotic Factors Regulate Soil Enzyme Activities at Plot and Microplot Scales Under Afforestation? - Qianxi Li; Ji Chen; Jiao Feng; Junjun Wu; Qian Zhang; Wei Jia; Qiaoling Lin; Xiaoli Cheng (Ecosystems, 2020)

Asymmetric response of soil methane uptake rate to land degradation and restoration: Data synthesis - Junjun Wu; Qiong Chen; Wei Jia; Chunyan Long; Wenzhi Liu; Guihua Liu; Xiaoli Cheng (Global Change Biology, 2020)
Land degradation and restoration profoundly affect soil CH 4 uptake capacity in terrestrial ecosystems. However, a comprehensive assessment of the response of soil CH 4 uptake to land degradation and restoration at global scale is not available. Here, we present a global meta‐analysis with a database of 228 observations from 83 studies to investigate the effects of land degradation and restoration on the capacity of soil CH 4 uptake. We found that land degradation significantly decreased the capacity of soil CH 4 uptake, except the conversion of pasture to cropland where the soil CH 4 uptake rate showed no response. In contrast, all types of land restoration significantly increased the capacity of soil CH 4 uptake. Interestingly, the response of soil CH 4 uptake rate to land degradation and restoration was asymmetric: the increased soil CH 4 uptake rate in response to the land restoration was smaller compared to the decrease in CH 4 uptake rate induced by the land degradation. The effect of land degradation on soil CH 4 uptake rate was not dependent on the time since land use change, but the CH 4 sink strength increased with the time since land restoration. The response of soil CH 4 uptake rate to both land degradation and restoration was predominantly regulated by changes in the soil water‐filled pore space, soil bulk density, and pH, whereas alterations in the substrate quantity and quality had negligible effect. Additionally, the effects of land degradation and restoration on soil CH 4 uptake were strongly related to the mean annual precipitation and soil texture. Overall, our results provide novel insights for understanding of how land degradation and restoration can affect the CH 4 sink strength of upland soils, and more importantly, our findings are beneficial to take measures to enhance the potential of soil CH 4 uptake in response to global land use change.

The miR-15/16 Cluster Is Involved in the Regulation of Vertebrate LC-PUFA Biosynthesis by Targeting pparγ as Demonostrated in Rabbitfish Siganus canaliculatus - Junjun Sun; Cuiying Chen; Cuihong You; Yang Liu; Hongyu Ma; Óscar Monroig; Douglas R. Tocher; Shuqi Wang; Yuanyou Li (Marine Biotechnology, 2020)

Contrasting soil C and N dynamics inferred from δ13C and δ15N values along a climatic gradient in southern China - Jiao Feng; Fan Yang; Junjun Wu; Qiong Chen; Qian Zhang; Xiaoli Cheng (Plant and Soil, 2020)

Soil labile and recalcitrant carbon and nitrogen dynamics in relation to functional vegetation groups along precipitation gradients in secondary grasslands of South China - Adugna Feyissa; Fan Yang; Jiao Feng; Junjun Wu; Qiong Chen; Xiaoli Cheng (Environmental Science and Pollution Research, 2020)

Co-expression Network Analysis Revealing the Potential Regulatory Roles of lncRNAs in Alzheimer’s Disease - Jiong Wu; Linhui Chen; Chaobo Zheng; Shanhu Xu; Yuhai Gao; Junjun Wang (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Cr(VI) removal performance from aqueous solution by Pseudomonas sp. strain DC-B3 isolated from mine soil: characterization of both Cr(VI) bioreduction and total Cr biosorption processes - Junjun Chang; Shengjiong Deng; Yun Liang; Jinquan Chen (Environmental Science and Pollution Research, 2019)

A probabilistic method for evaluating wedge stability based on blind data theory - Zhongjun Ma; Shengwu Qin; Junjun Chen; Jiangfeng Lv; Jianping Chen; Xiaolan Zhao (Bulletin of Engineering Geology and the Environment, 2019)

Performance of near real-time Global Satellite Mapping of Precipitation estimates during heavy precipitation events over northern China - Sheng Chen; Junjun Hu; Asi Zhang; Chao Min; Chaoying Huang; Zhenqing Liang (Theoretical and Applied Climatology, 2019)

Devonian integrative stratigraphy and timescale of China - Wenkun Qie; Xueping Ma; Honghe Xu; Li Qiao; Kun Liang; Wen Guo; Junjun Song; Bo Chen; Jianfeng Lu (Science China Earth Sciences, 2019)

Carboniferous integrative stratigraphy and timescale of China - Xiangdong Wang; Keyi Hu; Wenkun Qie; Qingyi Sheng; Bo Chen; Wei Lin; Le Yao; Qiulai Wang; Yuping Qi; Jitao Chen; Zhuoting Liao; Junjun Song (Science China Earth Sciences, 2019)

Composition, mixing state, and size distribution of single submicron particles during pollution episodes in a coastal city in southeast China - Lingling Xu; Xin Wu; Zhenyu Hong; Yanru Zhang; Junjun Deng; Youwei Hong; Jinsheng Chen (Environmental Science and Pollution Research, 2019)

Dual-functionality of RASSF1A overexpression in A375 cells is mediated by activation of IL-6/STAT3 regulatory loop - Mei Yi; Wei Wang; Shengnan Chen; Ya Peng; Junjun Li; Jing Cai; Ying Zhou; Qian Peng; Yuanyuan Ban; Zhaoyang Zeng; Xiaoling Li; Wei Xiong; et al. (Molecular Biology Reports, 2018)

Nitrogen Removal Performance and Enzyme Activities of Baffled Subsurface-Flow Constructed Wetlands with Macrophyte Biomass Addition - Junjun Chang; Shengjiong Deng; Wei Jia; Peng Chen; Yao Wang; Jinquan Chen (Water, Air, & Soil Pollution, 2018)

Vimentin is a crucial target for anti-metastasis therapy of nasopharyngeal carcinoma - Wei Wang; Mei Yi; Renya Zhang; Junjun Li; Shengnan Chen; Jing Cai; Zhaoyang Zeng; Xiaoling Li; Wei Xiong; Li Wang; Guiyuan Li; Bo Xiang (Molecular and Cellular Biochemistry, 2018)

Sustained-release study on Exenatide loaded into mesoporous silica nanoparticles: in vitro characterization and in vivo evaluation - Cuiwei Chen; Hongyue Zheng; Junjun Xu; Xiaowei Shi; Fanzhu Li; Xuanshen Wang (DARU Journal of Pharmaceutical Sciences, 2017)

Stability assessment of a new antithrombotic small peptide, Arg-Gly-Asp-Trp-Arg (RGDWR), and its derivative - Lijun Yang; Litao Zhang; Lihong Yan; Haifeng Zheng; Peifen Lu; Junjun Chen; Jie Dai; Haibiao Sun; Yong Xu; Tao Yang (Biotechnology Letters, 2017)

A Shinella β-N-acetylglucosaminidase of glycoside hydrolase family 20 displays novel biochemical and molecular characteristics - Junpei Zhou; Zhifeng Song; Rui Zhang; Caihong Chen; Qian Wu; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Nanyu Han; Zunxi Huang (Extremophiles, 2017)

Land scale biogeography of arsenic biotransformation genes in estuarine wetland - Si‐Yu Zhang; Jian‐Qiang Su; Guo‐Xin Sun; Yunfeng Yang; Yi Zhao; Junjun Ding; Yong‐Shan Chen; Yu Shen; Guibing Zhu; Christopher Rensing; Yong‐Guan Zhu (Environmental Microbiology, 2017)
Summary As an analogue of phosphorus, arsenic (As) has a biogeochemical cycle coupled closely with other key elements on the Earth, such as iron, sulfate and phosphate. It has been documented that microbial genes associated with As biotransformation are widely present in As‐rich environments. Nonetheless, their presence in natural environment with low As levels remains unclear. To address this issue, we investigated the abundance levels and diversities of aioA , arrA , arsC and arsM genes in estuarine sediments at low As levels across Southeastern China to uncover biogeographic patterns at a large spatial scale. Unexpectedly, genes involved in As biotransformation were characterized by high abundance and diversity. The functional microbial communities showed a significant decrease in similarity along the geographic distance, with higher turnover rates than taxonomic microbial communities based on the similarities of 16S rRNA genes. Further investigation with niche‐based models showed that deterministic processes played primary roles in shaping both functional and taxonomic microbial communities. Temperature, pH, total nitrogen concentration, carbon/nitrogen ratio and ferric iron concentration rather than As content in these sediments were significantly linked to functional microbial communities, while sediment temperature and pH were linked to taxonomic microbial communities. We proposed several possible mechanisms to explain these results.

Spatiotemporal distribution and source apportionment of low molecular weight organic acids in wet precipitation at a coastal city, China - Wenjiao Du; Zhenyu Hong; Yanting Chen; Junjun Deng; Jinsheng Chen; Lingling Xu; Youwei Hong; Hang Xiao (Environmental Science and Pollution Research, 2017)

Greenhouse wastewater treatment by baffled subsurface-flow constructed wetlands supplemented with flower straws as carbon source in different modes - Junjun Chang; Luyao Ma; Jinquan Chen; Yifeng Lu; Xiaoyun Wang (Environmental Science and Pollution Research, 2017)

The role of the PM2.5-associated metals in pathogenesis of child Mycoplasma Pneumoniae infections: a systematic review - Wei Hou; Xijin Xu; Yongge Lei; Junjun Cao; Yu Zhang; Liang Chen; Xia Huo (Environmental Science and Pollution Research, 2016)

Secreted expression of truncated capsid protein from porcine circovirus type 2 in Pichia pastoris - Xiaohong Chen; Junjun Chen; Yuanxing Zhang; Ping Zhu; Yong Deng; Qin Liu (Biotechnology Letters, 2016)

Paleogene lacustrine dolomitization, Xingou region, southern Qianjiang Depression, China - Junjun Shen; Bo Chen; Fangfang Chen; Chao Cheng; Yangfan Li; Ying Tian (Geosciences Journal, 2016)

Integrating lidar with Landsat data for subalpine temperate forest aboveground carbon estimation - Jun Du; Zhibin He; Longfei Chen; Junjun Yang; Xi Zhu; Weijun Zhao (International Journal of Remote Sensing, 2015)

The Effect of Streptozotocin and Alloxan on the mRNA Expression of Rat Hepatic Transporters In Vivo - Ting Zhai; Junjun Wang; Lijuan Sun; Yong Chen (AAPS PharmSciTech, 2015)

Detecting the effects of climate change on canopy phenology in coniferous forests in semi-arid mountain regions of China - Jun Du; Zhibin He; Junjun Yang; Longfei Chen; Xi Zhu (International Journal of Remote Sensing, 2014)

Cryptococcal Meningitis in Patients with Autoimmune Hemolytic Anemia - YaLi Yang; Junjun Sang; Weihua Pan; Lin Du; Wanqing Liao; Jianghan Chen; Yuanjie Zhu (Mycopathologia, 2014)

Müller Glia Cells Activation in Rat Retina After Optic Nerve Injury: Spatiotemporal Correlation with Transcription Initiation Factor IIB - Yue Xu; Chen Chen; Nan Jin; Juming Zhu; Lihua Kang; Tianqiu Zhou; Junjun Wang; Aiqin Sheng; Jian Shi; Zhifeng Gu; Aimin Sang (Journal of Molecular Neuroscience, 2013)

Distribution of MICB diversity in the Zhejiang Han population: PCR sequence-based typing for exons 2–6 and identification of five novel MICB alleles - Yanling Ying; Yanmin He; Sudan Tao; Zhedong Han; Wei Wang; Nanying Chen; Junjun He; Wei Zhang; Ji He; Faming Zhu; Hangjun Lv (Immunogenetics, 2013)

Molecular cloning and characterization of a tropinone reductase from Dendrobium nobile Lindl - Wei Chen; Xiaofei Cheng; Zhenhua Zhou; Junjun Liu; Huizhong Wang (Molecular Biology Reports, 2013)

Determination of GABAAα1 and GABAB1 receptor subunits expression in tissues of gilts during the late gestation - Zhiyong Fan; Yonghui Chen; Junjun Wang; Jinping Deng; Dexing Hou; Tiejun Li; Lingyuan Yang; Zhonghua Liu; Xiaosong Wu (Molecular Biology Reports, 2013)

Involvement of transcription initiation factor IIB in the light-induced death of rat retinal ganglion cells in vivo - Aimin Sang; Yue Xu; Nan jin; Tianqiu Zhou; Junjun Wang; Juming Zhu; Chen Chen; Jian Shi; Jie Shuai; Guofeng Xu; Zhifeng Gu (Journal of Molecular Histology, 2013)

Application of land-use change model in guiding regional planning: A case study in Hun-Taizi River Watershed, Northeast China - Miao Liu; Yuanman Hu; Wei Zhang; Junjun Zhu; Hongwei Chen; Fengming Xi (Chinese Geographical Science, 2011)

Ubiquitination of PCNA and Its Essential Role in Eukaryotic Translesion Synthesis - Junjun Chen; William Bozza; Zhihao Zhuang (Cell Biochemistry and Biophysics, 2011)

A 796 bp PsPR10 gene promoter fragment increased root-specific expression of the GUS reporter gene under the abiotic stresses and signal molecules in tobacco - Xiangbin Xu; Sai Guo; Kai Chen; Hongmiao Song; Junjun Liu; Longbiao Guo; Qian Qian; Huizhong Wang (Biotechnology Letters, 2010)

Eco-toxic effects of sulfadiazine sodium, sulfamonomethoxine sodium and enrofloxacin on wheat, Chinese cabbage and tomato - Caixia Jin; Qiuying Chen; Ruilian Sun; Qingxiang Zhou; Junjun Liu (Ecotoxicology, 2009)

Homologous-Restraint Polymerase Chain Reaction: An Efficient and Rapid Protocol to Clone Multiple Homologous Genes - Ming Chen; Honglei Liu; Yunfeng Bai; Zhenghong Zhang; Junjun Liu; Yuzhen Zhang (Current Microbiology, 2008)

Isolation and identification of a gene in response to rice blast disease in rice - Xianwu Zheng; Xuewei Chen; Xiaohong Zhang; Zhongzhuan Lin; Junjun Shang; Jichen Xu; Wenxue Zhai; Lihuang Zhu (Plant Molecular Biology, 2004)